Elementary students’ HOTS and attitude in environmental education: Sub topic of biology about disaster - Ilmi Zajuli Ichsan; Lufty Hari Susanto; Ati Kusmawati; Eva Dwi Kumalasari (Jurnal Biolokus, 2023)
needs to be learned by elementary school students. The problem of this drought disaster has an impact on the sustainability of people's lives, including impacting elementary school students. Capabilities such as Higher Order Thinking Skills (HOTS) which are implemented in the form of an attitude of caring for the environment need to be developed. The purpose of this study was to describe HOTS scores and environmental care attitudes of elementary school students on the topic of drought and environmental care attitudes. The results of this study indicate that students' HOTS scores are still in the low category (27.70). As for the attitude of caring for the environment is in the moderate category (69.12). Environmental education needs to be developed to increase HOTS and environmental care attitudes related to drought disasters which have an impact on public health. The conclusion of this study is that students' HOTS scores are still in the low category and environmental care attitudes are still in the moderate category.